Freedom from equine infectious anaemia virus infection in Spanish Purebred horses - Cruz, Fatima (Vet Rec Open, 2015)
INTRODUCTION: No cases of equine infectious anaemia (EIA) have been reported in Spain since 1983. Factors that could increase the risk of reintroducing equine infectious anaemia virus (EIAV) into Spain include the recent occurrence of the disease in Europe and the absence of compulsory serological testing before importation into Spain. AIMS AND OBJECTIVES: Given the importance of the Spanish Purebred (SP) horse breeding industry in Spain, the aim of this cross-sectional study was to provide evidence of freedom from EIAV in SP stud farms in Central Spain. MATERIALS AND METHODS: Serum samples from 555 SP horses, collected between September 2011 and November 2013, were tested using a commercially available EIAV ELISA with a published sensitivity of 100 per cent. RESULTS: All 555 samples were negative for antibody to EIAV, providing evidence of a true EIAV seroprevalence between 0 per cent and 0.53 per cent (95% CIs of the sensitivity and specificity of the ELISA technique used Q10 were 100 per cent and 99.3 per cent, respectively) among the SP breeding population in Central Spain. CONCLUSIONS: These findings should serve to increase confidence when exporting SP horses to other countries.